2016
DOI: 10.1103/physrevd.94.126004
|View full text |Cite
|
Sign up to set email alerts
|

Schwinger pairs production in a soft-wall model

Abstract: The Schwinger pairs production rate is calculated numerically in the soft-wall model with the help of a simpler method in determining the soft-wall's position beyond which probe strings connecting the Schwinger pairs do not fall into. The critical behaviour of the production rate and linear part in the middle region are both studied carefully. The latter manifests interesting new features. The results are compared with those in previous hard-wall models.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
(104 reference statements)
0
1
0
Order By: Relevance
“…It was found that the potential barrier will vanish and the Schwinger effect occurs when the external electric field E is equal or greater than the critical field E c . The production rate of pairs has been discussed in [13][14][15][16][17]. [18] has studied the production of the pairs in the non-supersymmetric QCD background.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the potential barrier will vanish and the Schwinger effect occurs when the external electric field E is equal or greater than the critical field E c . The production rate of pairs has been discussed in [13][14][15][16][17]. [18] has studied the production of the pairs in the non-supersymmetric QCD background.…”
Section: Introductionmentioning
confidence: 99%